Determinants of Underwriting Surplus of Tabarru’ Funds in Sharia Life Insurance Companies and Business Units in Indonesia - Muti’ah Hajar Izzati; Resfa Fitri; Mutiara Probokawuryan; Mohammad Iqbal Irfany (SMART Insight, 2026)
The surplus underwriting of tabarru’ funds is a crucial indicator for measuring the effectiveness and sustainability of Islamic life insurance companies’ operations. A well-performing Islamic life insurance company can be identified by its ability to generate a surplus underwriting. However, several companies have experienced underwriting deficits, indicating suboptimal management of participants' funds. This study aims to analyze the development of surplus underwriting in Islamic life insurance in Indonesia and the factors influencing it, using a panel data regression approach. The results, based on the Fixed Effect Model approach, show that all variables simultaneously have a significant effect on surplus underwriting. Partially, premium income and inflation have a significant positive effect on surplus underwriting, while investment returns, claims, and interest rates do not show a significant influence. These findings highlight the importance of strengthening participant fund management strategies to ensure the sustainability of surplus underwriting in tabarru’ funds.